The handbook of sustainable refurbishment : non-domestic buildings - Baker, Nick (London ; Sterling, VA : Earthscan, 2009)
Table of contents:#Part I 1: Strategies for sustainable refurbishment. ##Part II 2: Floors 3: Walls 4: Roofs 5: Windows 6: Atria and Double Skins 7: Mechanical Plant and Controls 8: Renewable Energy Options ##Part III: Case Studies 9. The Albatros, Den Hedler, Nedtherlands 10. Lycee Chevrollier, Angers, France 11. Daneshill House, Stevenage, UK 12. Ministry of Finance Offices, Athens 13. The Meyer Hospital, Florence, Italy
Includes bibliographical references and index.
boek